Strategies for Teaching Reading to Students with High and Low Vocabularies: Emphasizing Gist and Graphic Organizers - Fiki Setiawan; Yuni Awalaturrohmah Solihah (Asian Journal of Management, Entrepreneurship and Social Science, 2023)
The focus of this study was to investigate the effectiveness of Gist and Graphic Organizers in teaching reading to students with different levels of vocabulary proficiency. This study used a quasi-experimental methodology with a 2x2 factorial design to examine university-level English language learners. Two experimental subjects were involved. Gist and Graphic Organizer materials were used as instructional tools for data collection. Additionally, an observation was made to validate the data findings. According to the research findings, Gist and Graphic Organizers were helpful in teaching reading to students with different vocabulary competence levels. However, the results suggested that the Gist technique benefits both pupils with high and low vocabulary skills. Observation also revealed that students found the Gist technique more engaging and participatory. The lexical proficiency of students had a substantial impact on instructional materials, mainly when the Gist technique was applied. It has a significant impact on the reading comprehension of students. In teaching reading comprehension, the Gist method was adequate for students with a high vocabulary competency, while graphics Organizers was adequate for learner with a low vocabulary proficiency.